Efficacy of an Amphipathic Oligopeptide to Shuttle and Release a cis-Acting DNA Decoy into Human Cells - L. Citti; P. Rovero; M.G. Colombo; L. Mariani; L. Poliseno; G. Rainaldi (BioTechniques)
We investigated the ability of an amphipathic oligopeptide to carry a synthetic ds- DNA oligonucleotide inside human cells. The oligonucleotide was designed as a decoy binding site for the transcriptional activator of the methylguanine-DNA methyltransferase (MGMT) gene. The complex oligopeptide and decoy were administered to MCF10A exponentially growing cells, and the uptake was monitored by flow cytometry. After a 1-h exposure, almost all of the MCF10A cells were fluorescent, indicating that all of the cells had been transfected. By increasing the time, the fluorescence intensity per cell rapidly increased to a plateau at the 8-h time point. RT-PCR analysis of the MGMT gene was used as the molecular readout of the intracellular activity of the DNA decoy. MCF10A cells transfected with the oligopeptide/decoy complex showed a strong reduction in MGMT mRNA. Here, we discuss the advantages of using amphipathic oligopeptides as carriers of short DNA sequences.